PENYAKIT TUNGRO PADA TANAMAN PADI (Oryza sativa) DI KECAMATAN TABA PENANJUNG : INSIDENSI PENYAKIT DAN DETEKSI VIRUS SECARA MOLEKULER - Abdul Fiddin; Mimi Sutrawati; Hendri Bustamam; Dwi Wahyuni Ganefianti; Sipriyadi Sipriyadi (BPFP Universitas Bengkulu, 2021)
[TUNGRO DISEASE ON RICE PLANT (Oryza sativa) IN TABA PENANJUNG DISTRICT: DISEASE INCIDENCE AND MOLECULAR DETECTION OF VIRUSES]. Tungro is one of the important diseases of rice plants. Tungro disease caused by Rice tungro bacilliform virus (RTBV) and Rice tungro spherical virus (RTSV). This research aims to obtain information on the spread of the disease, vector population, and molecular detection by polymerase chain reaction method. This research was conducted from December 2019 to April 2020 in rice fields in Taba Penanjung sub-district, Bengkulu Tengah district at ± 540 meters above sea level and virus detection in the Laboratory of Biotechnology and Genetics Department of Biology Faculty of Mathematics and Natural Sciences (MIPA) and Laboratory of Plant Protection, Agriculture Faculty, Bengkulu University. Data analysis used descriptive analysis. The results showed that the highest disease incidence on the seven weeks after planting (wap) is 1.7% and the highest population of the vector on the 7 wap with an average of 7.7 vector/100m2 in the village of Taba Penanjung. Detection of viruses with the PCR method with the specific primer DAF/DAR succeeded in amplification of DNA band measuring 1,400 bp. RTSV was not detected by RT- PCR using a specific primer or RTSV. The result of this detection shows that the symptoms of tungro on rice plants in the cultivation of Taba Penanjung district associated with RTBV infection. RTSV unable to detect can be caused by many factors in the detection process, including total RNA extraction, cDNA synthesis, DNA amplification, and DNA visualization of PCR products.